Accessing the Impact of Socioeconomic Factors on Suicide : A Panel Study in ASEAN Countries - Hon, Kwang Hui; Jerome Kueh, Swee Hui; Shirly Wong, Siew Ling (2023)
This paper aims to investigate the impact of socioeconomic factors on suicide using panel data for 10 ASEAN countries over the time period 2000 to 2019. The linear and non-linear nexus between socioeconomic factors (GDP per capita, current health expenditure, unemployment rate fertility rate, female labour force participation rate and alcohol consumption per capita) and ASEAN suicide rate are investigated using a panel data from the World Health Organization and World Bank Data. The analysis conducted based on the panel unit root test, Pedroni cointegration test and panel ARDL estimation. The panel unit root tests showed the mixed results that the variables are stationary at I(0), I(1) or both. The Pedroni cointegration test found that there is a long-run relationship between variables in ASEAN countries. The findings of panel ARDL estimation indicates that all the variables are significant with ASEAN age-standardized total suicide rate. In addition, GDP per capita had U-shaped connection with age-standardized total suicide rate.